Evaluación del efecto de la proporción de ilmenita/carbón activado sobre la remoción de azul de metileno en un fotorreactor a escala laboratorio (2019)
In the present work, the proportion of ilmenite and activated carbon was evaluated for the removal of methylene blue, for this, initially test discs of 0.5 g were made, which were subjected to visible light and bubbling in 25 mL test reactors, in order to determine which disc allowed the greatest removal of dye and the number of uses necessary to achieve this goal, later, a photoreactor of 456 mL was built, which was monitored by the ARDUINO program, within this photoreactor, there were rings with samples of 2 g of the photocatalytic mixture and by using a TSL 2591 sensor attached to an ARDUINO UNO R3 card, it was possible to obtain the lighting level data (lux) in a computer. The purpose was to determine the composition that managed to remove more than 90% of colorant. When performing this experiment, it was obtained that the mixture that provided the best methylene blue removal was the one that contained 50% I - 50% AC.